2014
DOI: 10.1371/journal.pone.0086909
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Glycan Receptors for Minute Virus of Mice in Permissive Cell Lines Towards Understanding the Mechanism of Cell Recognition

Abstract: The recognition of sialic acids by two strains of minute virus of mice (MVM), MVMp (prototype) and MVMi (immunosuppressive), is an essential requirement for successful infection. To understand the potential for recognition of different modifications of sialic acid by MVM, three types of capsids, virus-like particles, wild type empty (no DNA) capsids, and DNA packaged virions, were screened on a sialylated glycan microarray (SGM). Both viruses demonstrated a preference for binding to 9-O-methylated sialic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…While the MGAT1 - CHO cell line was similarly sensitive to the MVMp strain as wild type CHO-S cells, it was resistant to MVMc infection (Table 2). The receptor protein for MVM have not yet been identified, but it has been demonstrated that MVMp binds to sialic acid residues from both N and O linked glycosylation (5557). Knocking out MGAT1 does not alter the O-linked glycosylation pathway, perhaps explaining why the line remains sensitive to MVMp.…”
Section: Resultsmentioning
confidence: 99%
“…While the MGAT1 - CHO cell line was similarly sensitive to the MVMp strain as wild type CHO-S cells, it was resistant to MVMc infection (Table 2). The receptor protein for MVM have not yet been identified, but it has been demonstrated that MVMp binds to sialic acid residues from both N and O linked glycosylation (5557). Knocking out MGAT1 does not alter the O-linked glycosylation pathway, perhaps explaining why the line remains sensitive to MVMp.…”
Section: Resultsmentioning
confidence: 99%
“…For other members, for example H-1 Parvovirus (H-1PV), LuIII, MVM, and Porcine Parvovirus (PPV), SIA binding is essential for infection and the recognition is to N-acetyl neuraminic acid. MVM utilizes terminal SIA on an unknown glycoprotein for cellular recognition [4] and binds specifically to α2-3 N-linked sialylated glycans including the s(Le x ) 3 motif [81,82]. This Lewis X motif is over expressed in cancer cells and likely dictates MVM's oncotropism [83].…”
Section: Glycans Receptor Utilization By the Autonomous Parvoviruses mentioning
confidence: 99%
“…For instance, the Feline and Canine parvoviruses, belonging to the genus Protoparvovirus , require the transferrin receptor for the entry process [ 26 ]. Regarding the Rodent protoparvovirus species, sialic acid has been identified as an important mediator for cell membrane recognition and entry for the MVM and H-1PV viruses [ 27 - 29 ], though the cognate cell receptors remain to be identified.…”
Section: Introductionmentioning
confidence: 99%